Choosing Between Left Ventricular Assist Devices and Biventricular Assist Devices - Sajad Shehab (Radcliffe Medical Media, 2019)
Right ventricular failure following left ventricular assist devices implantation is a serious complication associated with high mortality. In patients with or at high risk of developing right ventricular failure, biventricular support is recommended. Because univentricular support is associated with high survival rates, biventricular support is often undertaken as a last resort. With the advent of newer right ventricular and biventricular systems under design and testing, better differentiation is required to ensure optimal patients care. Clear guidelines on patient selection, time of intervention and device selection are required to improve patient outcomes.